KERAGAMAN DEWAN DALAM PENGAMBILAN KEPUTUSAN INVESTASI: LEBIH EFISIEN ATAU TIDAK? - Stefanus; Reynald Emmanuel Dwistia; Vito Raphael Hadyana; Joni (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The objective of this research is to examine the relationship between gender and investment efficiency levels in the context of developing countries, specifically focusing on companies listed on the Indonesia Stock Exchange during the period of 2020-2021. It is important to determine whether there is a significant influence on the efficiency levels of companies. By employing regression analysis, this study did not find any significant impact between gender diversity and investment efficiency. The results indicate a negative correlation, suggesting that gender diversity in large-sector companies reduces investment efficiency.